Efficacy of the intranasal route for the administration of NPY1R and its effects on the treatment of neurodegenerative and mood disorders via heteroreceptor complexes formation - Molina-Sánchez, Diana Desirée; Moreno-Madrid, Isabel; Arrabal-Gómez, José Carlos; Díaz-Sánchez, Estela; Barbancho-Fernández, Miguel Ángel; Sánchez-Pérez, Jose Andrés; Blanco-Reina, Encarnación; Beltrán-Casanueva, Rasiel; Bayolo-Guanche, Juan Vicente; Tomé-García, Mónica; Carazo-Barrios, Lina; Reyes-Bueno, Jose Antonio; et al. (My University, 2025)
Dysregulation of adult hippocampal neurogenesis has been implicated in currently highly prevalent neuropsychiatric disorders such as major depressive disorder (MDD) or cognitive decline such as Alzheimer's disease (AD). The neuropeptide Y1 receptor (Y1R) of neuropeptide Y (NPY) has been found to interact with galanin receptor 2 (GALR2) in certain areas of the hippocampus with effects on memory processes and mood-related behaviour within 24 hours of intranasal administration. This study addresses the synergistic effects of the long-term NPY1R-GALR2 interaction on both mood-related behaviour and cognitive function following intranasal co-administration, as well as exploring other interactions of NPY1R. These changes have been assessed at molecular, cellular and behavioural levels. GALR2 and/or NPY1R agonists were administered intranasally, while other cohort of rats received ketamine and/or NPY1R agonist. Behaviour was assessed using the Forced Swimming Test (FST) to analyse antidepressant activity and the object-in-place task for spatial memory. In brain slices, we performed in situ PLA techniques to detect GALR2-NPYY1R and NPY1R- TrkB heteroreceptor complexes formation, as well as different immunolabelling techniques with proliferating cell nuclear antigen (PCNA), doublecortin (DCX), bromodeoxyuridine (BrdU) and brain-derived neurotrophic factor (BDNF). The results show that the interaction of NPYY1R with both GALR2 and TrkB enhances antidepressant behaviour and spatial memory, while increasing the formation of heteroreceptor complexes (GALR2-NPYY1R or NPY1R-TrkB) in the dentate gyrus of the hippocampus. Both treatments promote neuroblast proliferation, survival as well as neuronal differentiation and maturation. In addition, co-stimulation of NPY1R-TrkB enhances BDNF expression. Our results contribute to the understanding of neuroplasticity mediated by the formation of NPY1R-GALR2 and NPY1R-TrkB heteroreceptor complexes following intranasal administration of NPY1R and GALR2 agonists, highlighting their role in enhancing the processes of neurogenesis, neuronal survival and maturation. These findings open up new therapeutic approaches for the treatment of MDD and AD.
Keywords: Sistema nervioso - Degeneración; Trastornos afectivos; Heteroreceptor complexes; Mood disorders; Neurodegenerative diseases; NPY1R; GALR2